Loss of GDF10/BMP3b as a prognostic marker collaborates with TGFBR3 to enhance chemotherapy resistance and epithelial‐mesenchymal transition in oral squamous cell carcinoma. Issue 5 (1st March 2015) - Cheng, Chieh‐Wen; Hsiao, Jenn‐Ren; Fan, Chi‐Chen; Lo, Yu‐Kang; Tzen, Chi‐Yuan; Wu, Li‐Wha; Fang, Wei‐Yu; Cheng, Ann‐Joy; Chen, Chung‐Hsing; Chang, I‐Shou; Jiang, Shih Sheng; Chang, Jang‐Yang; et al.
Abstract : Growth differentiation factor‐10 (GDF10), commonly referred as BMP3b, is a member of the transforming growth factor‐β (TGF‐β) superfamily. GDF10/BMP3b has been considered as a tumor suppressor, however, little is known about the molecular mechanism of its roles in tumor suppression in oral cancer. Clinical significance of GDF10 downregulation in oral squamous cell carcinoma (OSCC) was evaluated using three independent cohorts of OSCC patients. The molecular mechanisms of GDF10 in the suppression of cell survival, cell migration/invasion and epithelial‐mesenchymal transition (EMT) were investigated by using oral cancer cell lines. The present study shows that GDF10 is downregulated during oral carcinogenesis, and GDF10 expression is also an independent risk factor for overall survival of OSCC patients. Overexpression of GDF10 attenuates cell proliferation, transformation, migration/invasion, and EMT. GDF10‐inhibited EMT is mediated by ERK signaling but not by typical TGF‐β signaling. In addition, overexpression of GDF10 promotes DNA damage‐induced apoptosis and sensitizes the response to all‐trans retinoic acid (ATRA) and camptothecin (CPT). Intriguingly, the expression of GDF10 is induced by type III TGF‐β receptor (TGFBR3) through TGF‐β‐SMAD2/3 signaling. Our findings suggest that TGFBR3 is an upstream activator of GDF10 expression and they share the same signaling to inhibit EMT and migration/invasion. These results support that GDF10 acts as a hinge to collaborate with TGFBR3 in the transition of EMT‐MET program. Taken together, we illustrated the clinical significance and the molecular mechanisms of tumor‐suppressive GDF10 in OSCC. © 2015 Wiley Periodicals, Inc.